HCV micro-elimination in individuals with HIV in the Netherlands 4 years after universal access to direct-acting antivirals: a retrospective cohort study. Issue 2 (February 2021) - Smit, Colette; Boyd, Anders; Rijnders, Bart J A; van de Laar, Thijs J W; Leyten, Eliane M; Bierman, Wouter F; Brinkman, Kees; Claassen, Mark A A; den Hollander, Jan; Boerekamps, Anne; Newsum, Astrid M; Schinkel, Janke; et al.
Summary: Background: In the Netherlands, access to direct-acting antivirals (DAAs) against hepatitis C virus (HCV) has been unrestricted for chronic infection since 2015. We evaluated whether the nationwide incidence of HCV infections in individuals with HIV has changed since 2015. Methods: In this retrospective cohort study, data from the ATHENA cohort of people with HIV aged 18 years or older attending any of the 24 HIV treatment centres in the Netherlands between 2000 and 2019 were assessed. We used parametric proportional hazards models with a piecewise exponential survival function to model HCV primary infection and reinfection incidence per 1000 person-years. Findings: Of the 23 590 individuals without previous HCV infection, 1269 cases of HCV primary infection were documented (incidence 5·2 per 1000 person-years [95% CI 5·0–5·5]). The highest incidence was observed in men who have sex with men (MSM; 7·7 per 1000 person-years [7·3–8·2]) and was lower in people who inject drugs (PWID; 1·7 per 1000 person-years [0·7–4·1]) and other key populations (1·0 per 1000 person-years [0·8–1·2]). In MSM, incidence increased in 2007 to 14·3 per 1000 person-years and fluctuated between 8·7 and 13·0 per 1000 person-years from 2008 to 2015. In 2016, incidence declined to 6·1 cases per 1000 person-years and remained steady between 4·1 and 4·9 per 1000 person-years from 2017 to 2019. Of the 1866 individuals with a previous HCV infection, 274 reinfections were documented (incidence 26·9 per 1000 person-years [95% CI 23·9–30·3]). The highest incidence rate was observed in MSM (38·5 per 1000 person-years [33·9–43·7]) and was lower in PWID (10·9 per 1000 person-years [3·5–33·8]) and other key populations (8·9 per 1000 person-years [6·3–12·5]). In MSM, reinfection incidence fluctuated between 38·0 and 88·9 per 1000 person-years from 2006 to 2015, reaching 55·6 per 1000 person-years in 2015. In 2016, reinfection incidence declined to 41·4 per 1000 person-years, followed by further decreases to 24·4 per 1000 person-years in 2017 and 11·4 per 1000 person-years in 2019. Interpretation: The sharp decline in HCV incidence in MSM with HIV shortly after restrictions on DAAs were lifted suggests a treatment-as-prevention effect. HCV incidence was already low in PWID and other groups before unrestricted access. Ongoing HCV transmission is occurring in MSM, as illustrated by a declining but high rate of reinfection, stressing the need for additional preventive measures. Funding: Dutch Ministry of Health, Welfare, and Sport.